Novel assays to assess the prevalence and neutralizing potential of anti-IdeS antibodies in healthy humans - Hannachi, Emna; Trecco, Amélia; Daventure, Victoria; Delignat, Sandrine; Bonilla, Perrine; Lecerf, Maxime; Thaunat, Olivier; Dimitrov, Jordan D.; Deligne, Claire; Lacroix-Desmazes, Sébastien (Frontiers in Immunology, 2026)
BackgroundThe IgG-degrading enzyme IdeS (imlifidase) is a cysteine protease produced by Streptococcus pyogenes. It specifically hydrolyzes human IgG, cleaving the molecule to separate the F(ab’)2 fragment from the Fc region, thereby promoting IgG catabolism. The therapeutic form of IdeS (Idefirix®) is currently approved for use in patients undergoing kidney transplantation to eliminate donor-specific IgG, and in patients with Goodpasture syndrome to remove pathogenic anti-glomerular basement membrane antibodies. IgG antibodies directed against IdeS have been previously reported in both healthy individuals and kidney transplant recipients. However, the occurrence and potential clinical significance of anti-IdeS IgA antibodies and IdeS neutralizing antibodies have not been thoroughly investigated.MethodsIn this study, we developed semi-quantitative enzyme-linked immunosorbent assays, synthesized a specific IdeS substrate, and validated a quantitative neutralization assay to detect and quantify anti-IdeS IgG, IgA, and IdeS neutralizing antibodies in healthy human plasma and serum samples.ResultsWe demonstrate the presence of anti-IdeS IgG capable of neutralizing IdeS enzymatic activity in therapeutic preparations of pooled normal human IgG (IVIg). Anti-IdeS IgG and IgA antibodies were detected in the plasma and serum of over 85% of 136 healthy individuals. However, clinically significant levels of IdeS-neutralizing activity were found in only ~1% of the individuals tested. IdeS-neutralizing activity was mediated exclusively by IgG, not IgA, and did not systematically correlate with levels of anti-IdeS IgG.ConclusionsAnti-IdeS IgG and IgA are highly prevalent in the normal population. This may relate to repeated infection by S. pyogenes. However, we found a low prevalence of clinically relevant levels of IdeS neutralizing antibodies. These findings highlight the need for a prospective clinical trial to assess IdeS-binding and IdeS-neutralizing antibody levels in kidney transplant recipients. Our novel functional IdeS neutralization assay offers a predictive tool to guide personalized medicine and determine patient eligibility for IdeS-based desensitization protocols.